Adoption of Blockchain-Based Electronic Bills of Lading: Implications for Maritime Business Education and Industry Practice - Nur Achmad Jabrial, Sukardi, Mardiana (Meteor STIP Marunda, 2025)
This paper examines the adoption of blockchain-based electronic bills of lading (eBL) in container shipping from the dual perspective of industry practice and maritime business education. A conceptual model is developed to analyze how perceived usefulness, trust, regulatory clarity, and ecosystem readiness influence intentions to adopt eBL platforms among carriers, freight forwarders, and shippers. Data are obtained through a questionnaire survey of logistics professionals and follow-up interviews with early adopters. The results show which benefits—such as faster document handling, reduced disputes, and improved cargo visibility—are most valued, and which concerns—such as legal recognition, interoperability, and organizational resistance—remain obstacles. In parallel, syllabi from maritime business and logistics programs are reviewed to determine how digital trade documentation and blockchain concepts are currently taught. The study identifies gaps between industry needs and academic coverage, proposing updated teaching modules that include practical eBL case studies, mock transactions, and collaboration with platform providers. The paper argues that aligning education with technological change is essential to prepare graduates who can drive innovation in maritime trade documentation.